Notes on Russian architecture - Rappaport, Alexander (project baikal, 2023)
Authentic Russian architecture has not yet manifested itself in historical specimens. It is waiting to do it in the future. It is given in history only as an awakening, which has not taken on its own forms. The specificity of Russian architecture may be seen through Russian literature. Later on, the new lines of development in both language and architecture will be closely linked to the reform of urbanization and settlement processes.